Epigallocatechin-3-gallate enhances the osteoblastogenic differentiation of human adipose-derived stem cells - Zhang J; Wu K; Xu T; Wu J; Li P; Wang H; Wu H; Wu G (Dove Medical Press, 2019)
Jing Zhang,1 Kai Wu,2 Ting Xu,3 Jiajun Wu,1 Pengfei Li,1 Hong Wang,4 Huiling Wu,1 Gang Wu5 1Department of Plastic and Aesthetic Center, The First Affiliated Hospital of Zhejiang University, Hangzhou, Zhejiang, China; 2Spine Lab, Department of Orthopedic Surgery, The First Affiliated Hospital of Zhejiang University, Hangzhou, Zhejiang, China; 3Department of Stomatology, First Affiliated Hospital, Zhejiang University, Hangzhou, China; 4Department of Oral and Maxillofacial Surgery, Amsterdam University Medical Centre, University of Amsterdam and Vrije Universiteit Amsterdam, Amsterdam, North Holland, the Netherlands; 5Department of Oral Implantology and Prosthetic Dentistry, Academic Centre for Dentistry Amsterdam, University of Amsterdam and Vrije Universiteit Amsterdam, Amsterdam, North Holland, the Netherlands Purpose: The aim of this study is to investigate the effects of epigallocatechin-3-gallate (EGCG), a major polyphenol extracted from green tea, on the osteoblastogenic differentiation of human adipose-derived stem cells (hASCs).Patients and methods: hASCs were acquired from human adipose tissue. With informed consent, subcutaneous adipose tissue samples were harvested from periorbital fat pad resections from ten healthy female adults who underwent double eyelid surgery. hASCs were cultured in osteogenic medium with or without EGCG (1 µM, 5 µM, or 10 µM) for 14 days. We evaluated the effects of EGCG by quantifying cell growth, ALP activity (an early osteoblastogenic differentiation marker), BSP, OCN (a late osteoblastogenic differentiation marker), and extracellular matrix mineralization. We also performed Western blots to measure osteoblastogenesis-related proteins such as Runx2 and adipoblastogenesis-related transcription factors, such as STAT3, C/EBP-α, and PPAR-γ.Results: EGCG at 5 µM resulted in significantly higher cell proliferation and ALP activity than did the control on days 3, 7, and 14. On day 7, 5 µM EGCG significantly enhanced BSP expression. On day 14, EGCG at all concentrations promoted OCN expression. In addition, EGCG at 5 µM resulted in the highest level of extracellular matrix mineralization. On day 3, the expression levels of Runx2 were significantly higher in the 5 µM EGCG group than in the other groups, whereas later, on days 7 and 14, Runx2 expression levels in the EGCG group were significantly lower than those of the control group. EGCG at all three concentrations was associated with significantly lower levels of phosphorylated STAT3, C/EBP-α, and PPAR-γ.Conclusion: EGCG at 5 µM significantly enhanced the osteoblastogenic differentiation of hASCs. Keywords: EGCG, hASCs, osteoblastogenesis, STAT3, bone regeneration